2007
DOI: 10.1016/j.crte.2007.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Tethyan sutures in mainland Southeast Asia: New insights for Palaeo-Tethys closure and implications for the Indosinian orogeny

Abstract: Two contrasting parallel tectonic sutures can be recognised through the Yunnan-Thailand region of mainland Southeast Asia; they are sutures of the Devonian-Triassic Palaeo-Tethys Ocean and a Permian back-arc basin. The Changning-Menglian and Inthanon suture zones are regarded as the Palaeo-Tethys Suture Zone. The Jinghong-Nan-Sra Kaeo suture is regarded as a closed back-arc basin. The Sukhothai Zone is no longer treated as a part of the Sibumasu Terrane, but is defined as the core part of the Permian island-ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
409
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 543 publications
(458 citation statements)
references
References 56 publications
10
409
2
Order By: Relevance
“…The late Triassic suturing of the Palaeo-Tethys leading to the Indosinian Orogeny (Metcalfe, 2000 andMetcalfe, 2008) was followed by the suturing of the Neo-Tethys, the collision of the Indian plate with Asia, and the onset of the Himalayan Orogeny at ca. 50 Ma (Green et al, 2008).…”
Section: Geological Framework 21 Chiang Mai-lincang Beltmentioning
confidence: 99%
“…The late Triassic suturing of the Palaeo-Tethys leading to the Indosinian Orogeny (Metcalfe, 2000 andMetcalfe, 2008) was followed by the suturing of the Neo-Tethys, the collision of the Indian plate with Asia, and the onset of the Himalayan Orogeny at ca. 50 Ma (Green et al, 2008).…”
Section: Geological Framework 21 Chiang Mai-lincang Beltmentioning
confidence: 99%
“…Previous studies suggested two Paleo-Tethyan branches in SE Asia, namely the Main Paleo-Tethys represented by the ChangningMenglian-Inthanon suture Kamata et al, 2012), and the Ailaoshan Ocean represented by the Jingshajiang-Ailaoshan suture (Sone and Metcalfe, 2008;Zaw et al, 2014). It has been commonly accepted that the Main Paleo-Tethys had opened in the Silurian-Devonian and closed in the Triassic by an east-directed (modern orientation) subduction beneath Indochina-Simao (Metcalfe, 2013;Zaw et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The closure of the Paleo-Tethys was in the Middle Triassic (Sone et al, 2008), implying that there was accommodation space for a continuous deposition of sedimentary successions in the paleo-basin. Moreover, the global sea level for the Phanerozoic (Haq and Schutter, 2008) was on the rise from the Devonian to lower Carboniferous.…”
Section: Sedimentation History In the Paleo-tethysmentioning
confidence: 99%